(untitled) (Asian Journal of Agriculture, 2022)
Abstract. Satrio RD, Nikmah IA, Fendiyanto MH, Pratami MP, Awwanah M, Sari NIP, Farah N, Nurhadiyanta. 2022. Construction of an ultra-high-density consensus genetic map and analysis of recombination rate variation in Sorghum bicolor. Asian J Agric 6: 47-54. Sorghum is one of the most widely grown cereal crops on a global scale. A consensus map is a method for combining genetic information from multiple populations, and it is an effective way to increase genome coverage and marker density. This study constructed a consensus map by combining publicly available marker data from four mapping populations. A total of 3,449 non-redundant polymorphic markers at the nucleotide level were used to construct a single consensus map on ten sorghum chromosomes. This study generated an ultra-high-density sorghum consensus map consisting of many markers spanning 1,571.68 cM and averaging one marker per 0.46 cM. Due to the markers’ high density, only 0.06% of the markers had an interval greater than 5 cM. The local recombination rates were estimated using a set of all markers’ genetic and physical positions along each of the ten chromosomes. The analysis of the recombination rate on ten sorghum chromosomes revealed that it decreased as the centromere position was getting closer. The consensus map generated in this study can be used to integrate information related to sorghum genetic resources and QTLs into the genome sequence, thereby accelerating the discovery of novel potential genes in sorghum.